Implementasi Kebijakan Penyelenggaraan Kabupaten Layak Anak dalam Menanggulangi Kekerasan terhadap Anak di Kabupaten Solok Selatan - Nada Febri Novita; Lince Magriasti (Lembaga Yasin AlSys, 2026)
Violence against children remains a social problem that requires serious attention, including in South Solok Regency, although the local government has enacted Regional Regulation Number 1 of 2023 concerning the Implementation of Child-Friendly Regency as an instrument for child protection. This study aims to analyze the implementation of the Child-Friendly Regency policy in addressing violence against children in South Solok Regency. This study used a descriptive method with a qualitative approach through interview and documentation techniques. The data were analyzed through the stages of data reduction, data display, and conclusion drawing using George C. Edwards III’s policy implementation theory. The results show that the implementation of the Child-Friendly Regency policy in addressing violence against children has not been optimal. In the aspect of communication, policy socialization has been carried out, but it has not been consistent and has not been supported by the optimal use of information media. In the aspect of resources, there are still limitations in the number of human resources, the unavailability of child psychologists, and inadequate budget allocation. In the aspect of disposition, policy implementers have strong commitment, but community participation in preventing and reporting cases remains low. In the aspect of bureaucratic structure, cross-sectoral cooperation is already in place, but coordination among agencies has not been optimal. The conclusion of this study emphasizes that the effectiveness of the implementation of the Child-Friendly Regency policy requires strengthening policy communication, improving resource capacity, enhancing community participation, and optimizing cross-sectoral coordination so that child protection in South Solok Regency can be implemented more effectively.